Removal of necrotic alveolar part of mandible with CGF (Concentrated Growth Factors) application into a post-operative bone defect - a case report - Damian Chybicki; Anna Janas-Naze; Piotr Osica; Adrian Gnatek (Kazimierz Wielki University, 2019)
Usage of platelet concentrate is an interesting clinical option for enhancement of healing tissue. One of them - Concentrated Growth Factors (CGF) is produced by processing blood samples with a special centrifuge device. It is proven that this material contains high concentration of growth factors and CD34+ cells which have anti-inflammatory properties and ability to stimulate proliferation and differentiation of connective tissue cells and angiogenesis. The following article presents a case of 70-year-old-patient who underwent the augmentation of the post-operative bone defect with CGF after removal of necrotic alveolar part of the mandible.